KESEDIAAN KONSUMEN MEMBAYAR LEBIH DARI HARGA PEMBELIAN AYAM ORGANIK DI RANCH MARKET BASUKI RAHMAT SURABAYA (Agridevina : Berkala Ilmiah Agribisnis, 2022)
The development of demand for organic products is caused by public awareness to consume food products that are low in chemical residues as part of a tendency to live a healthy lifestyle and back to nature. Companies need to determine a price strategy that is suitable for consumers in Indonesia, research is needed that discusses how much consumers are able to pay ( WTP) for organic food products. Research Objectives 1) To analyze consumer interest in paying for organic chicken purchases at Ranch Market Surabaya; 2) Analyzing factors that influence consumers' willingness to pay for organic chicken at Basuki Rahmat's Ranch Market, Surabaya. The research data analysis method used WTP analysis with Contingent Valuation Method (CVM) and SEM PLS analysis. The average price that consumers can pay to benefit from organic chicken is Rp. 108,829.10 per head. The factors that influence consumer interest in paying for organic chicken are awareness and lifestyle variables that have a significant effect on willingness to pay for organic chicken at Basuki Rahmat Ranch Market Surabaya DOI : https://doi.org/10.33005/adv.v11i1.3093